Performance management in education : improving practice - Reeves, Jenny; Forde, Christine; O'Brien Jim; British Educational Leadership and Management Association (London : Thousand Oaks, Calif. : P. Chapman, 2002)
This book provides an overview of some of the key issues in developing professional performance and examines critically some of the key strategies that can be used to enhance professional performance.
Includes bibliographical references
Keywords: Teachers -- Great Britain; Performance standards -- Great Britain